Slovak Teachers’ Perception of Professional Self-Efficacy and Education of Pupils From Other Languages and Cultural Backgrounds - Cabanová, Mariana; Lynch, Zuzana (Pedagogika, 2023)
The study explores Slovak teachers in mainstream schools and their self-efficacy perception when it comes to educating learners from diverse language backgrounds. The research findings offer valuable insights into teachers’ perspectives, providing essential information for future teacher training aimed at improving the teaching of students from varied linguistic and cultural environments. A surprising revelation was that teachers without prior experience working with these students reported higher levels of self-efficacy.